2010
DOI: 10.3892/etm_00000084
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of human mammary cancer cells exposed to 27-hydroxycholesterol

Abstract: Abstract. the aim of the present study was to identify the possible mechanisms by which certain estradiol receptor (Er)-positive mammary tumor cells remain resistant to treatment with anti-estrogens or inhibitors of local estradiol (E 2 ) production. to this end, we compared the proliferative effects on mammary cancer cells of the novel selective Er modulator 27-hydroxycholesterol (27Ohc) to those of E 2 , and evaluated their inhibition by ici 182,780 (ici). analysis of the effects on the cell cycle of 27Ohc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…The same groups reported later on the detrimental activity of 27OHC on bone homeostasis (3,4). The proliferation of various ER-positive mammary cancer cell lines is also affected by 27OHC, as demonstrated by DuSell et al (2) and by us (5). Remarkably, the proliferation rate of nontumorigenic mammary MCF10 cells are not affected by the exposure to micromolar concentrations of 27OHC (5).…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…The same groups reported later on the detrimental activity of 27OHC on bone homeostasis (3,4). The proliferation of various ER-positive mammary cancer cell lines is also affected by 27OHC, as demonstrated by DuSell et al (2) and by us (5). Remarkably, the proliferation rate of nontumorigenic mammary MCF10 cells are not affected by the exposure to micromolar concentrations of 27OHC (5).…”
Section: Introductionmentioning
confidence: 71%
“…The proliferation of various ER-positive mammary cancer cell lines is also affected by 27OHC, as demonstrated by DuSell et al (2) and by us (5). Remarkably, the proliferation rate of nontumorigenic mammary MCF10 cells are not affected by the exposure to micromolar concentrations of 27OHC (5). Recently, we have demonstrated that the exposure of ER-positive epithelial mammary tumor cells to 2 µM 27OHC for longer than 48 h triggers their transition into a mesenchymal phenotype (6).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Thus, fluctuations in 27-OHC may modulate ER and potentially contribute to the pathogenesis of ER+ breast cancers. While it has been established that 27-OHC is an endogenous selective ER modulator (SERM) and that it exacerbates breast cancer pathophysiology [5, 9, 10], its role in molecular events following ER activation in the context of breast cancer pathogenesis is not fully understood.…”
Section: Introductionmentioning
confidence: 99%